Increased electro-convulsive therapy stimulus intensity and cognitive functioning in manic patients - Gopal, A.; Rathor, D. S.; Mohanty, S. (International Journal of Research in Medical Sciences, 2021)
Background: Temporary changes in cognitive functions after electro-convulsive therapy (ECT) have been documented. The researchers are exploring if increasing the stimulus intensity of ECT produce better recovery from psychopathology also trying to map effects of increased stimulus intensity on side effects profile including cognitive functions. In the present study, we are reporting effects of increased stimulus intensity of ECT on cognitive functions in manic patients. Methods: The present study is a prospective analytical case control study conducted in the department of psychiatry, Institute of Mental Health and Hospital, Agra, after getting clearance from hospital ethical committee. The study included 60 patients with the diagnosis of manic psychopathologyfrom May 2018 to September 2019. Sample was divided into two groups: 1.5 times of threshold and 2.0 times of threshold. The ECT was delivered as per specified protocol of the study. The scores on Montreal cognitive assessment (MoCA) were compared both within and between groups at baseline and follow up. Results: The results suggested that both level of stimulus intensity produced mild level of disruptions in cognitive functioning at follow ups and the higher stimulus intensity i.e. 2.0 times of threshold resulted in more impairment in cognitive functions. Conclusions: The impact of ECT by increasing its current intensity for two times, on cognitive functions as seen clinically, suggested no serious adverse effects on any of the patients included in the sample.